Comparison of solid and liquid fractions of pretreated Norway spruce as reductants in LPMO-supported saccharification of cellulose - Tang, Chaojun; Gandla, Madhavi Latha; Jönsson, Leif J. (Frontiers in Bioengineering and Biotechnology, 2022)
The role of lignin in enzymatic saccharification of cellulose involving lytic polysaccharide monooxygenase (LPMO) was investigated in experiments with the solid and liquid fractions of pretreated Norway spruce from a biorefinery demonstration plant using hydrothermal pretreatment and impregnation with sulfur dioxide. Pretreated biomass before and after enzymatic saccharification was characterized using HPAEC, HPLC, Py-GC/MS, 2D-HSQC NMR, FTIR, and SEM. Chemical characterization indicated that relatively harsh pretreatment conditions resulted in that the solid phase contained no or very little hemicellulose but considerable amounts of pseudo-lignin, and that the liquid phase contained a relatively high concentration (~5 g/l) of lignin-derived phenolics. As judged from reactions continuously supplied with either air or nitrogen gas, lignin and lignin fragments from both the solid and the liquid phases efficiently served as reductants in LPMO-supported saccharification. When air was used to promote LPMO activity, the enzymatic conversion of cellulose after 72 h was 25% higher in reactions with pretreated solids and buffer, and 14% higher in reactions with pretreatment liquid and microcrystalline cellulose. Research in this area is useful for designing efficient saccharification steps in biochemical conversion of lignocellulosic biomass.